Private Cloud Assistant Trust Model for P2P Secure Transactions - Wei Lin; Xianghan Zheng (Dianxin kexue)
Secure transactions among P2P peers are critical for system stability. Considering existing security breaches, a private cloud assistant trust model for P2P session negotiation and connection was proposed. With a few characteristics during computing and storage process（e.g. high efficiency, security, neutrality）, private cloud platform is capable to provide trustworthiness calculation, storage and evaluation for each peer in P2P network. Some coping mechanisms were proposed to curb malicious behaviors, such as low quality services, false recommendation and strategic fraud attaches. Simulation result shows that the proposed model has feasibility, efficiency and dynamic adaptability.